Landscape of agroecology financing - Wanyama, Rosina; Chege, Christine Kiria (2024)
There is an urgent need to transform the current food systems to be more resilient, sustainable, and inclusive. Agroecology is a promising approach that could address the multiple challenges associated with the current food systems. However, a significant share of national and global investments is still being allocated to conventional approaches (or the business-as-usual). Yet, the cost associated with agroecological transition is significantly lower when compared to the estimated cost of the negative externalities emanating from the current food systems. Like other countries in the Global South, Kenya faces significant challenges because of unsustainable food systems. Although the Country ranks second, after Ethiopia, in the amount of bilaterial and multilateral aid received, a significant share is allocated to industrial approaches. In response to these, the Government of Kenya recently launched its National Agroecology Strategy for Food Systems Transformation 2024 -2032 to promote an ecologically resilient and socially inclusive food system in the Country. Although the strategy recognises the need for increased investment in agroecology, it remains unclear how this will be achieved. Kenya benefits from consolidated funds from donors, such as the Agroecology Fund, but the size of such grants is still relatively small for a significant impact. It is therefore important for governments, donors, philanthropists, and other investors to redesign their investments portfolios and budgetary allocations to prioritize initiatives that promote agroecological transition. This may be achieved by either increasing funding for agroecological interventions vis-a-vis conventional/industrial approaches or shifting existing funds towards interventions that support agroecological transition, or a combination of both.